2022
DOI: 10.1155/2022/7479416
|View full text |Cite|
|
Sign up to set email alerts
|

Additional Acupuncture Confers a Favorable Long-Term Prognosis for Elderly Hypertensive Patients with Carotid Atherosclerosis after Atorvastatin Treatment

Abstract: Objective. The purpose of the study is to investigate the clinical efficacy and long-term prognosis of acupuncture (AP) combined with atorvastatin (ATO) in treating senile essential hypertension (EH) complicated with carotid atherosclerosis (CA). Methods. 108 elderly EH patients with CA admitted to our hospital between January 2018 and September 2018 were enrolled into the study, consisting of 67 patients who received treatment of AP with ATO (AP + ATO group) and 41 patients who received treatment of ATO alone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…It inhibits the synthesis of cholesterol and at the same time increases the expression of LDL receptors in the liver cell membrane, reduces the levels of cholesterol and lipoprotein, and increases liver LDL uptake and catabolism are increased by the number of cell surface LDL receptors. [ 10 ] Amlodipine is a dihydropyridine calcium channel antagonist, which can effectively inhibit the transfer of calcium ions into cardiomyocytes and smooth muscle cells. Our results showed that the combined treatment group after adding amlodipine was significantly better than the single treatment group in improving blood pressure, blood lipids, and overall disease efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It inhibits the synthesis of cholesterol and at the same time increases the expression of LDL receptors in the liver cell membrane, reduces the levels of cholesterol and lipoprotein, and increases liver LDL uptake and catabolism are increased by the number of cell surface LDL receptors. [ 10 ] Amlodipine is a dihydropyridine calcium channel antagonist, which can effectively inhibit the transfer of calcium ions into cardiomyocytes and smooth muscle cells. Our results showed that the combined treatment group after adding amlodipine was significantly better than the single treatment group in improving blood pressure, blood lipids, and overall disease efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] Its mechanism of action is to inhibit the rate-limiting enzyme hydroxyglutaryl coenzyme A reductase in the early stage of cholesterol synthesis. [ 10 ] At the same time, it can increase the expression of low-density lipoprotein (LDL) receptors in the liver cell membrane, reduce the levels of cholesterol and lipoprotein, and increase the uptake and catabolism mechanism of LDL by increasing the number of LDL receptors on the surface of liver cells. [ 11 ] In recent years, studies have confirmed that atorvastatin has good curative effect in improving ventricular myocardial function, vascular endothelial cell function and myocardial fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Acupuncture and moxibustion, as a traditional treatment method of Chinese medicine, In clinical practice and experimental studies for reducing blood pressure [ 2 ], Protect vascular endothelium [ 3 ], Alleviating cardiac function impairment [ 4 ], Reduce blood lipid and plaque formation [ 5 ], Improve sleep quality and other clinical symptoms showed an irreplaceable role[ 6 ]. Acupuncture is generally accepted as a treatment with few side effects and high safety.…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%